The Mindfulness-Based Social Work and Self-Care Programme: A Mixed Methods Evaluation Study. (21st October 2021) - Maddock, Alan; McCusker, Pearse; Blair, Carolyn; Roulston, Audrey
Abstract: During their social work education, students engage in a number of stressful learning activities, often simultaneously, which can negatively impact their well-being, mental health and social work practice. Mindfulness practices are beginning to be integrated into social work curricula globally to enhance student self-care along with key social work practice skills and values. This mixed methods study examined the effects of a bespoke six-week online mindfulness-based social work and self-care (MBSWSC) programme on the stress, burnout, well-being, anxiety and depression levels of thirty social work students from two universities in the UK. This study also examined the effects of MBSWSC on a number of mindfulness-based mediators of change in these outcomes. Participant perceptions of the benefits of the MBSWSC programme on their well-being and social work practice are further explored via a thematic analysis of an open-ended questionnaire. Statistically significant changes in all variables were found post-programme except for depression and loss of empathy/depersonalisation, a facet of burnout. The qualitative data provided a deeper insight into the potential benefits of the programme for the enhancement of student well-being, mental health and anti-oppressive social work practice (AOP). Abstract : Social work students can experience high levels of stress, burnout and reductions in their well-being and mental health during their training. This is due to students engaging in a range of learning activities, often at the same time, which can consistently push them out of their comfort zones. Self-care training has been recognised as a means of helping social work students to manage the demands of their education. Training social work students in mindfulness practices could help students to reduce the negative impacts of their education on them and also enhance their social work practice. This study examined an online six-week mindfulness-based programme for social work practice and self-care using both quantitative and qualitative methods. This study found that this programme reducedstress and feelings of burnout and improved the mental health and well-being of thirty social work students. The students who completed the programme highlighted in their qualitative evaluation of the programme that by completing the programme, their mental health and well-being improved, and their confidence in practicing social work more effectively increased.